LITERATURE AND HISTORY - Bharat Thakor, (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the history of Indian literature, the view of seeing literature and history as complementary to each other has been going on for thousands of years, that is, since our tradition. In Indian tradition, at one time, the entire writing was seen in the special context of poetry. That tradition continues in Sanskrit poetry till Jagannath. In ancient literature, history was known as the science of Puravritta, and scholars have identified Puravritta as the Vedas.